Promoción y prevención de salud bucal mediante propuestas didácticas en niños y niñas con discapacidad en la Unidad Educativa de Educación Especializada Ciudad de Loja # 2 durante el periodo septiembre 2019-marzo 2020 - Rojas Blacio, César David (2020)
This research study is of great importance since it allows us to focus on a sector of society that is often forgotten, which over the years has not received notable attention, showing the limitations and needs that children with disabilities have to have good oral health and maintain it in your daily life; Therefore, it is necessary to implement a program for the promotion and prevention of oral health, which allows us to teach them how to carry out proper hygiene. One of the main objectives of this research study is to promote oral health in children with disabilities in the "Educational Unit of Specialized Education Ciudad de Loja # 2"; It is a descriptive, observational, quantitative and cross-sectional study that, through the application of surveys validated by professors of the Dentistry career, adapted for easy interpretation, it was first sought to diagnose the knowledge that children had about care of the oral cavity, the first results lodged a percentage of 47.30%; and later an increase in the level of knowledge on the subject was evidenced since the results of the second survey reached a total average of 89.24% of correct answers. With the given program we can conclude that it was possible to improve the knowledge of the shared topics during the course of the research, this will prevent the progression of pathologies by improving their oral health, thus giving healthy minds and smiles. Key words: dentistry, pediatric dentistry, infants, program, pedagogical.